In vitro maturation is slowed in prepubertal lamb oocytes: ultrastructural evidences - Palmerini, Maria G (Reprod Biol Endocrinol, 2014)
BACKGROUND: In vitro maturation (IVM) of immature oocytes retrieved from unstimulated ovaries may avoid side effects connected to hyperstimulation during IVF procedures, including the risk of cancer recurrence. In humans, the scarce availability of immature oocytes limits morphological studies. The monovular ovine may represent an experimental model for IVM studies. METHODS: To assess if the scarce developmental competence of prepubertal oocytes (PO) is related to morphological changes we analyzed, by light and transmission electron microscopy, cumulus-oocyte-complexes (COCs) from lambs (30-40 days old) and sheep (4-6 years old) at sampling and after 7 h, 19 h, 24 h of IVM. Meiotic progression was determined at the same time points. RESULTS: At sampling, the germinal vesicle (GV) of PO was round and centrally or slightly eccentrically located, whereas in adult oocytes (AO) it was irregularly shaped and flattened against the oolemma. PO, differently from AO, showed numerous trans-zonal projections. Organelles, including cortical granules (CGs), were more abundant in AO. After 7 h, the percentage of AO that underwent GVBD-MI transition increased significantly. In PO, the oolemma was juxtaposed to the ZP; in AO, it showed several spikes in correspondence of cumulus cells (CC) endings. In PO, organelles and isolated CGs were scattered in the ooplasm. In AO, groups of CGs were also present under the oolemma. After 19 h, PO underwent GVBD-MI transition; their oolemma showed several spikes, with CC projections retracted and detached from the ZP. AO underwent MI-MII transition; their oolemma regained a round shape. CGs were located beneath the plasmalemma, arranged in multiple, continuous layers, sometime discontinuous in PO. After 24 h, both groups reached the MII-stage, characterized by a regular oolemma and by expanded CCs. PO showed CGs distributed discontinuously beneath the oolemma, while AO showed a continuous monolayer of CGs. CONCLUSIONS: Even if PO were able of reaching morphological maturation after 24 h of IVM, our ultrastructural analysis allowed detecting the presumptive sequence of cytoplasmic alterations connected with the delay of nuclear maturation, that might explain the reduced developmental competence of such oocytes. Data from the sheep model are of interest for zootechny, and provide an experimental basis for improving human IVM technology.